Time trends in incidence and prevalence of carpal tunnel syndrome over eight years according to multiple data sources: Pays de la Loire study - Roquelaure, Yves; Chazelle, Emilie; Gautier, Ludivine; Plaine, Julie; Descatha, Alexis; Evanoff, Bradley; Bodin, Julie; Fouquet, Natacha; Catherine, Buisson (Scandinavian Journal of Work, Environment & Health, 2017)
' ' OBJECTIVE ': 'The aim of this study was to describe time trends of incidence/prevalence of carpal tunnel syndrome (CTS), one of the most common musculoskeletal disorders, in a French region over an 8-year period. ' ' METHODS ': 'Three independent data sources were analyzed for the population of the Pays de la Loire region aged 20–59 between 2004 and 2011: hospital discharge records for “surgically treated CTS” (SURG-CTS), the social insurance data on “CTS compensated for as an occupational disease” (OD-CTS), and the regional surveillance program of “work-related diseases” (WRD-CTS). Case counts were analyzed using negative binomial regression models and cubic spline curves with year as the main covariate. ' ' RESULTS ': 'The annual incidence rates of SURG-CTS decreased from 3.35 to 2.98 per 1000 person-years over the 8-year period, with an overall declining trend [-2.00%, 95% confidence interval (95% CI) -3.07– -0.91%), P<0.001]. The annual incidence rate of OD-CTS per 1000 person-years decreased (from 1.52 to 1.01) between 2004 and 2007 and increased after 2007 (from 1.45 to 2.34), with an overall gain of 54% during the study period. The prevalence rate of WRD-CTS decreased from 5.04 (95% CI 3.90–6.13) to 3.08 (95% CI 2.11–4.06) per 1000 employed person-years, with a non-significant trend between 2004 and 2011. Conclusion The study showed declining rates of SURG-CTS and WRD-CTS in the population of working age between 2004 and 2011, contrasting with increasing rate of OD-CTS after 2007. More research and surveillance data are needed to assess whether and to what extent the declining rates of CTS are actually attributable to improvement in working conditions and/or to non-occupational factors.
Keywords: carpal tunnel syndrome; CTS; incidence; occupational disease; Pays de la Loire study; prevalence; surgery; surveillance; time trend